2016
DOI: 10.7189/jogh.06.010404
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and determinants of antenatal care utilization: analysis of national survey data in seven countdown countries

Abstract: BackgroundAntenatal care (ANC) is critical for improving maternal and newborn health. WHO recommends that pregnant women complete at least four ANC visits. Countdown and other global monitoring efforts track the proportions of women who receive one or more visits by a skilled provider (ANC1+) and four or more visits by any provider (ANC4+). This study investigates patterns of drop–off in use between ANC1+ and ANC4+, and explores inequalities in women’s use of ANC services. It also identifies determinants of ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
84
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(130 citation statements)
references
References 32 publications
29
84
2
5
Order By: Relevance
“…It therefore, supports the study of Arthur [15] that wealth still influences the ANC use in Ghana even after the introduction of the free maternal health policy. This finding is, therefore, in agreement with works of Pandey and Singh [47], Saad-Haddad et al [35], and Yadav and Kesarwani [5] that the occupational status of expectant mothers significantly influences their maternal care use.…”
Section: Discussion Of Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It therefore, supports the study of Arthur [15] that wealth still influences the ANC use in Ghana even after the introduction of the free maternal health policy. This finding is, therefore, in agreement with works of Pandey and Singh [47], Saad-Haddad et al [35], and Yadav and Kesarwani [5] that the occupational status of expectant mothers significantly influences their maternal care use.…”
Section: Discussion Of Resultssupporting
confidence: 93%
“…This empowers pregnant mothers to increase control over the things which affect their lives as far their healthcare needs are concerned. In their study on the socioeconomic determinants of maternal healthcare utilisation in seven countries, Saad-Haddad et al [35] reveal that household wealth significantly influenced the facility type for accessing maternal care. Abekah-Nkrumah and Abor [36] and Rai et al [37] also found out that household income is linked with frequent use of modern healthcare.…”
Section: Related Literaturementioning
confidence: 99%
“…The prevalence of women who registered for antenatal during the last pregnancy is similar to the National average and to prevalence found in other studies carried out in the South West and South East of Nigeria [7,15,18,19], but higher than findings in studies carried out in Northern Nigeria [13,14]. These figures are however much lower than those of many Asian and subSaharan countries [20][21][22].…”
Section: Discussionsupporting
confidence: 81%
“…Early initiation of ANC and receipt of four visits are likely to be correlated because it is more difficult to achieve the prescribed higher number of visits if a woman initiates ANC late. In addition to receiving essential interventions, studies demonstrate that women who attend ANC early and frequently are more likely to utilize skilled providers for ANC and delivery care than those who do not (22,31). Some of the reasons for late and less frequent ANC utilization among pregnant adolescents in SSA include financial barriers, lack of information about the risks of pregnancy and benefits of ANC, stigma within the community, and disrespectful treatment by health workers (21,(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%